2018
DOI: 10.3390/ani8100171
|View full text |Cite
|
Sign up to set email alerts
|

“I Feel Sorry for Them”: Australian Meat Consumers’ Perceptions about Sheep and Beef Cattle Transportation

Abstract: Simple SummaryUnderstanding what concerns about animal welfare are most prominent among members of the public is critical to improve processes in the meat production industry. Hence, this study uses qualitative data to explore how Australian meat consumers viewed one aspect of the production process, livestock transportation. Participants in this study were concerned about the close packing of animals into trucks and ships, and their experiences during long-distance voyages; their views on this topic may be mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…The presence of a nudge does not result in a specific cost or loss to the individual, rather it is there to make a self-desired choice easier [47]. If some citizens, as research has shown [3,4,14], express a desire to improve the lives of farm animals, then the purpose of nudging is to make that desired intention easier to fulfill and action where it matters (i.e., when they are making decisions as a consumer). For those citizens who have absolutely no desire to engage in pro-animal welfare behaviours, then the nudge should not constrain their free-choice.…”
Section: Behavioural Initiatives To ‘Nudge’ Pro-animal Welfare Behmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a nudge does not result in a specific cost or loss to the individual, rather it is there to make a self-desired choice easier [47]. If some citizens, as research has shown [3,4,14], express a desire to improve the lives of farm animals, then the purpose of nudging is to make that desired intention easier to fulfill and action where it matters (i.e., when they are making decisions as a consumer). For those citizens who have absolutely no desire to engage in pro-animal welfare behaviours, then the nudge should not constrain their free-choice.…”
Section: Behavioural Initiatives To ‘Nudge’ Pro-animal Welfare Behmentioning
confidence: 99%
“…Increasing public concern for the welfare of farm animals is well documented [1,2,3]. Yet, this growing interest in the lives of farm animals does not correspond with an increase in demand for higher welfare products [4].…”
Section: Introductionmentioning
confidence: 99%
“…Citizen concern regarding animal welfare has been increasing in many parts of the world [1]; in general, consumers are more sensitive regarding the way farm animals are kept and handled [2,3,4]. Harper and colleagues reported that “animal welfare is used by consumers as an indicator of important product attributes, such as safety and the impact on health” [3].…”
Section: Introductionmentioning
confidence: 99%
“…The response rate and a possible bias in the sample of respondents (e.g., people without internet access cannot answer) are recognized issues when using online surveys to collect stakeholders’ opinion [20]. Other possible problems are: incomplete questionnaires resulting in incomplete data collection [21], and surveys with answers provided (closed-ended surveys) could not reflect all the possible answers of the respondents [1]. Open-ended questions may overcome this last problem, as they allow respondents to use their own words to express their feelings, attitudes and understanding of the subject and to include more information and details [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation